STAGING BRUTALITY: REPRESENTATION OF VIOLENCE IN MANJULA PADMANABHAN’S LIGHTS OUT - Nakathorige, Khairunnisa; A Dar, Masrook A Dar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines Manjula Padmanabhan’s Lights Out, a play that explores the intersections of urban alienation, moral apathy, and the representation of violence. Inspired by a real-life incident, the play uses an offstage act of brutality—a woman’s rape—as its central event, challenging conventional depictions of violence on stage. Employing Johan Galtung’s framework of direct and structural violence, the analysis highlights how Padmanabhan critiques the urban middle class’s detachment and complicity through inaction. The play’s deliberate decision to keep violence unseen shifts focus to the ethical and psychological dimensions of spectatorship, invoking Laura Mulvey’s concept of the gaze to examine passive complicity. By juxtaposing physical and psychological violence, Padmanabhan underscores societal indifference as both cause and consequence of systemic failures. Through stark staging and unsettling soundscapes, Lights Out compels audiences to confront their own roles in perpetuating societal violence and moral paralysis.